Locally non-uniform oxidation in self-terminating thermal oxidation assisted wet etching technique for AlGaN/GaN heterostructure - Liu, Jingqian; Wang, Jinyan; Xu, Zhe; Jiang, Haisang; Yang, Zhenchuan; Wang, Maojun; Min Yu; Xie, Bing; Wu, Wengang; Ma, Xiaohua; Zhang, Jincheng; Hao, Yue (ELECTRONICS LETTERS, 2015)
The oxidation mechanism in self-terminating wet etching technique with thermal oxidation of AlGaN layer followed by etching in KOH solution is investigated. Spike-shape remnants of oxidised AlGaN are observed at the initial stage of wet etching in KOH solution, which could be completely etched away after enough etching time. Transmission electron microscope/energy dispersive spectroscopy analysis indicates the existence of crystalline AlGaN inside the remnants. Finally, a possible explanation is given that the oxide channels from AlGaN surface towards AlGaN/GaN interface generated during thermal oxidation are firstly etched away at the initial stage of KOH wet etching, then after enough time these remnants with non-c axis crystal orientation surfaces exposed to KOH solution could be completely etched away leaving GaN layer beneath unaffected, which realises self-terminating etching.